Population pharmacokinetics and model-based dosing evaluation of bedaquiline in multidrug-resistant tuberculosis patients - Shao, Ge; Bao, Ziwei; Davies Forsman, Lina; Paues, Jakob; Werngren, Jim; Niward, Katarina; Schön, Thomas; Bruchfeld, Judith; Alffenaar, Jan-Willem; Hu, Yi (Frontiers in Pharmacology, 2023)
Aims Bedaquiline is now recommended to all patients in the treatment of multidrug-resistant tuberculosis(MDR-TB) using standard dosing regimens. As the ability to measure blood drug concentrations is very limited, little is known about drug exposure and treatment outcome. Thus, this study aimed to model the population pharmacokinetics as well as to evaluate the currently recommended dosage. Methodology A bedaquiline population pharmacokinetic(PK) model was developed based on samples collected from the development cohort before and 1,2,3,4,5,6,8,12,18 and 24 hours after drug intake on week 2 and week 4 of treatment. In a prospective validation cohort of patients with MDR-TB, treated with bedaquiline-containing standardized regimen, drug exposure was assessed using the developed population PK model and thresholds were identified by relating to 2-month and 6-month sputum culture conversion and final treatment outcome using classification and regression tree analysis. In an exploratory analysis by the probability of target attainment(PTA) analysis, we evaluated the recommended dosage at different MIC levels by Middlebrook 7H11 agar dilution(7H11). Results Bedaquiline pharmacokinetic data from 55 patients with MDR-TB were best described by a three-compartment model with dual zero-order input. Body weight was a covariate of the clearance and the central volume of distribution, albumin was a covariate of the clearance. In the validation cohort, we enrolled 159 patients with MDR-TB. The 7H11 MIC mode(range) of bedaquiline was 0.06 mg(0.008-0.25 mg/L). The study participants with AUC0-24h/MIC above 175.5 had a higher probability of culture conversion after 2-month treatment(adjusted relative risk, aRR:16.4;95%CI:5.3-50.4). Similarly, those with AUC0-24h/MIC above 118.2 had a higher probability of culture conversion after 6-month treatment(aRR:20.1;95%CI: 2.9-139.4), and those with AUC0-24h/MIC above 74.6 had a higher probability of successful treatment outcome (aRR:9.7;95%CI:1.5-64.8). Based on the identified thresholds, simulations showed that the WHO recommended dosage(400mg once daily for 14 days followed by 200mg thrice weekly) resulted in PTA>90% for the majority of isolates (94%;MICs<0.125 mg/L). Conclusion We established a population PK model for bedaquiline in patients with MDR-TB in China. Based on the thresholds and MIC distribution derived in a clinical study, the recommended dosage of bedaquiline is sufficient for the treatment of MDR-TB.